ANALYSIS OF TWITTER SOCIAL MEDIA FUNCTIONS IN RESPONDING TO THE CIANJUR EARTHQUAKE IN INDONESIA - Gusti Naufal Rizky Perdana; Andi Muhammad Rifqi Rusli; Yaen Miftakhul Laily (FAKULTAS DAKWAH UIN SALATIGA, 2023)
Social media Twitter as a place to respond disaster events that build an effective place to disseminate the latest information and communication users to discuss the current disaster. This research focuses on exploring the intensity of tweets related to analyzing the disaster content of tweets in discussions of the Cianjur earthquake on Twitter social media. This research uses a Qualitative Data Analysis (QDA) approach, which helps to know the network, content, and cloud using the Nvivo 12 Plus software. The study results stated that the intensity of the conversation on Twitter social media related to the Cianjur earthquake received a relatively high response from various groups, especially public officials and government agency accounts. Twitter social media is also a place to think about grief and prayer, increase solidarity to assist, and become a media that reports condition quickly gives limitedgreetings online, and assist directly victims through donations